What Drives Africa's Inability to Comply with EU Standards? Insights from Africa's Institution and Trade Facilitation Measures - Fatima Olanike Kareem; Inmaculada Martínez-Zarzoso; Bernhard Brümmer (The European Journal of Development Research, 2022)
Over the years, there have been a significant number of Africa's food exports rejected at the European Union (EU) borders due to their non-compliance with EU food safety standards. This paper, therefore, provides an in-depth investigation of the potential causes of the non-compliance of Africa's food exports to EU food standards and the subsequent rejection of such food exports at its borders. We contribute to the literature by investigating the roles played by trade facilitation measures and institutions in food export rejections and also exclusively provide a more detailed analysis and specific evidence at the product level. Our results indicate that poor trade facilitation measures, particularly inefficient border and food logistics procedures in African countries, increase the incidence of food rejection at the EU border and add to Africa's challenges in accessing EU markets. Thus, non-compliance with EU food safety standards can be addressed by African governments through the strengthening of their domestic institutions and trade facilitation measures, with policies that improve logistics and border procedures as well as measures that align their food standards to international ones. This will ensure an efficient food supply chain that meets international food safety standards and facilitates food trade.
Keywords: Q17; Q18; F13; F14; L1; 330; Food safety standards; Food exports; Logistics procedures; Infrastructure; Institutional quality